Autonomous Choice and the Right to Know One's Genetic Origins - Ravitsky, Vardit (The Hastings Center report, 2014)
In “The Ethics of Anonymous Gamete Donation: Is There a Right to Know One's Genetic Origins?,” Inmaculada de Melo-Martín deconstructs the interests the right is supposed to protect. She argues that these interests are not set back or thwarted when one has no access to one's genetic origins. The basis of her argument is that we lack robust empirical evidence that donor-conceived individuals suffer certain alleged harms, and that even when such harms are present, they do not provide strong enough justification to ground the right. Indeed, the research on the needs, preferences, and well-being of donor-conceived individuals is scant. In fact, we lack robust empirical evidence regarding all aspects of donor conception. I argue, however, that the right to know one's genetic origins does not rest on empirical evidence. Some donor-conceived individuals who are unable to know their genetic origins may suffer great harms. Others may suffer no harm at all. But all are treated wrongly when they are deprived of the ability to access information about their genetic origins. They are deprived of an important aspect of their autonomy: the liberty to choose what meaning they assign to the genetic components of their identity.